The lexicon and culture: culture and the lexicon - Reichmann, Oskar (Lexicographica, 2023)
The article analyzes the relationship between lexicon and culture , first from a description theoretical perspective. The focus is on a conception of these two under aspects of technical language, particularly with regard to the relationship between noun and verb-based technical language. Subsequently, an attempt is made to derive culture from speech, specifically from the linguistic action within a language community, while taking into account hermeneutic problems. In closing the article explains how the unity of word usage and culture can be presented and communicated to a target audience by the FWB, a semantically-oriented dictionary. The lemma glaube in its definition 4 serves as an example.
Gesehen am 08.01.2024